Foundations of wellness - Reger-Nash, Bill, 1942- (Human Kinetics, 2015)
In Foundations of Wellness, you'll explore physical, mental, emotional, social, environmental, and spiritual realms of wellness; discover wellness strategies; and learn how to make healthy behavioral changes. Foundations of Wellness will help you achieve balance and peace of mind in your life.- Resumé vydavatel